KATA TANYA DALAM BAHASA INGGRIS DAN BAHASA SANGER DIALEK SIAU (SEBUAH ANALISIS KONTRASTIF) - RAWUNG, VABIOLA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study is an attempt to identify, classify, analyze and contrast of English and Sanger language in Siau dialect which focuses on the interrogative sentences in relation to their forms and functions in both languages. The writer analyzed interrogative sentences based on the concept of Quirk (1985), and contrasted them by using Lado’s theory (1957). The data collected in Sanger language in Siau dialect is twenty hundred and fifty. The result showed that forms of interrogative sentences in English are yes-no question, wh-question and alternative question. English and Sanger language in Siau dialect have similarity that the form of yes-no question exit at the beginning of sentence. The differences of both languages are in form and function.English has three forms of interrogative sentences such as yes-no question, wh-question and alternative question. Sanger language in Siau dialect also has three question forms such as yes-no question (Botonge, tengade, haruse, trusekre) wh-question (Koapa, kengere, suapa, kerapa, sai, mekapura) and alternative question Keywords: English, Siau Language, interrogative sentence, contrast